Choroidal Vascularity in Non-arteritic Anterior Ischaemic Optic Neuropathy. (3rd September 2019) - Guduru, Abhilash; Abdul Rasheed, Mohammed; Goud, Abhilash; Ashik, Mohamed; Kumar, Vupparaboina Kiran; Chhablani, Jay; Badakere, Akshay; Kekunnaya, Ramesh; Patil-Chhablani, Preeti
ABSTRACT: This study evaluates the peripapillary choroidal vascularity in eyes with non-arteritic anterior ischaemic optic neuropathy (NAION) and compares it with the vascularity of healthy fellow eyes and age-matched subjects. The peripapillary choroidal vascularity index (CVI), a new tool of measurement, was calculated using horizontal swept-source optical coherence tomography scans. CVI was calculated using a previously validated automated algorithm. CVI in NAION and fellow eyes of NAION patients were compared with age-matched eyes of healthy individuals using Kruskal–Wallis test. A total of 20 eyes of 20 patients with acute unilateral NAION with healthy fellow eyes (20 eyes) and 40 eyes of 40 healthy patients were included in the study. The average age of patients with NAION was 56 ± 8 and 55 ± 7 years in age-matched healthy controls. NAION eyes had a significantly lower CVI than age-matched controls in both nasal and temporal areas. NAION nasal CVI was 0.47 ± 0.47 compared to 0.62 ± 0.04 in controls ( p < 0.001). NAION temporal CVI was 0.45 ± 0.48 compared to 0.58 ± 0.04 in controls ( p < 0.001). Temporal CVI was 0.45 ± 0.48 in NAION eyes and was significantly lower than counterpart healthy fellow eyes 0.48 ± 0.02 ( p = 0.007). In conclusion, NAION eyes have significantly reduced vascularity in the peripapillary area. CVI is lower in the nasal and temporal of the optic disc compared to healthy individuals. This may suggest those with smaller CVI are more prone to ischaemia from reduced vascularity resulting in NAION.